Georgia Architectural and Historic Properties Survey of 513 Second Ave., Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 513 Second Ave., Valdosta, Ga. One story house of irregular plan, multi-gabled roof, shed porch with square posts. Interior and exterior chimney. Shiplap siding. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: App. 1900-1910.Typical vernacular house located in a district of similar houses built around early 1900's. Has significance as part of a potential N.R. district.
1 electronic record and derivatives. 1 PDF. 3 scans. 85.6 MB (89,783,145 bytes). 1 photograph digitized from original negative. 2400 DPI TIF. 300 DPI 4x6 JPG.
Keywords: Electronic records; Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)